Study of exotic decay of Cs isotope close to the proton drip line. (December 2020) - Das, P.; Dattaf, Ushasi; Chakraborty, S.; Rahman, A.; Borge, M.J.G.; Tengblad, O.; Andreyev, A. N.; Becerril, A.; Bhattacharya, P.; Bhattacharyya, A.; Cederkall, J.; Witte, H. De; et al.
Abstract: The neutron-deficient 115 Cs was produced at ISOLDE, CERN by spallation reaction using 1.4 GeV proton on LaC2 target. The exotic decay modes were studied by using a charged particle array (DSSD and pad detectors) and a γ -detector array (four Clovers) at the ISOLDE decay station (IDS). In this report, results on observed β -delayed particle emission from 115 Cs, a nucleus close to proton drip line, is presented. By measuring the time distribution in the delayed proton spectrum, the half-life of the ground state of 115 Cs was extracted. The obtained half-life is in agreement with previous reported value. For the first time, the p-unbound states of 115 Xe, obtained by measuring beta-delayed protons from 115 Cs is reported.